Beyond Combustion: Innovative Utilizations of Agricultural Residues - Hareesh, Dhara; Sridhar, Rathod (Chronicle of Bioresource Management, 2025)
India generates nearly 500 million tonnes of crop residues annually, positioning it among the world’s largest producers. Traditionally regarded as waste, residues are increasingly recognized as critical inputs for enhancing soil fertility, nutrient cycling, and sustainable agroecosystem functioning. However, residue burning remains prevalent, resulting in the volatilization of up to 80% nitrogen and 25% phosphorus, elevated particulate emissions, and long-term soil quality deterioration. Crop residue management (CRM) strategies are broadly classified into on-farm and off-farm pathways. On-farm practices, including surface mulching, in-situ incorporation, and microbial consortia-based interventions such as Pusa Decomposer, enhance soil organic carbon, microbial activity, and crop productivity. Off-farm utilizations encompass livestock feed, mushroom cultivation, and bedding material. Advanced valorization technologies such as biochar production, composting (e.g., Suchitha method), and biogas recovery promote nutrient recycling and energy generation. Industrial applications in pulp, briquette, bio-brick, and bioelectricity production further integrate CRM within a circular bioeconomy, advancing climate-resilient and sustainable agricultural systems.